The role of the anterior insula in social norm compliance and enforcement: Evidence from coordinate-based and functional connectivity meta-analyses. (September 2018) - Bellucci, Gabriele; Feng, Chunliang; Camilleri, Julia; Eickhoff, Simon B.; Krueger, Frank
Highlights: Different anterior insula (AI) regions underlie social behaviors in economic games. Dorsal AI activation is related to expectancy of norm compliance. Ventral AI is associated with negative feelings motivating norm enforcement. Abstract: Economic games —trust (TG) and ultimatum game (UG)— combined with fMRI have shown the importance of the anterior insula (AI) in social normative behaviors. However, whether different AI subregions are engaged in different cognitive and affective processes for social norm compliance and norm enforcement during social exchange remains elusive. Here, we investigated the role of the dorsal AI (dAI) and ventral AI (vAI), combining a coordinate-based meta-analysis of fMRI studies using the TG and UG with meta-analytic task-based and task-free connectivity analyses. Our findings showed that the right dAI and vAI were the only common brain regions consistently activated across games. These clusters were part of two functionally distinguishable connectivity networks associated with cognitive (dAI) and emotional (vAI) processes. In conclusion, we propose that dAI mediates cognitive processes that generate expectancy for norm compliance, whereas vAI mediates aversive feelings that generate motivation to norm enforcement. The identified functional differentiation of the right AI in the social domain contributes to a better understanding of its role in basic and clinical neuroscience.